Proyek “Melukis di Atas Talenan” Terintegrasi STEAM-Tri N Untuk Mengembangkan Kreativitas Siswa - Lestariningsih, Dwi; Bariyah, Insanul Qisti (Universitas Muhammadiyah Magelang, 2024)
One of the skills required for 21st century skills is creative thinking skills. Creative thinking is inseparable from the term creativity. Low student creativity is caused by the use of methods, models, and learning strategies that do not support students' creativity. The purpose of this study was to describe the real conditions of the STEAM-Tri N Integrated